Framing Media Daring dalam Pemberitaan Demonstrasi Penolakan Revisi RUU Pilkada 2024: Analisis pada Tempo.co dan BeritaSatu.com Periode Agustus 2024 - Ardiansyah, Firman; Zamzamy, Ahmad (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines media coverage of demonstrations rejecting the revision of the 2024 Regional Head Election Bill (RUU Pilkada). Two national online media, Tempo.co and BeritaSatu.com, used different framing approaches. The aim is to identify and compare their framing constructions. The method applied was Robert N. Entman’s framing analysis with four elements: define problems, diagnose causes, make moral judgement, and treatment recommendations. Data were taken from online news in August 2024. The findings show that Tempo.co emphasized democracy, criticism of the government, and civil society voices, while BeritaSatu.com highlighted political stability, public order, and government responses. These differences demonstrate how editorial orientation shapes media reality and public opinion. Theoretically, this research enriches studies on reality construction in Indonesian mass media. Practically, it encourages readers and policymakers to be more critical of news framing. The novelty lies in revealing contrasting framings between progressive and pro-government media on the 2024 Pilkada, reflecting the tension between democracy and stability.